Experimental investigation and multi-objective optimization of cryogenic Friction-stir-welding of AA2014 and AZ31B alloys using MOORA technique. (December 2022) - Boopathi, Sampath
Abstract: The cryogenic Friction Stir Welding (CFSW) experimental setup has been designed and fabricated to supply the low-temperature liquid nitrogen supply to perform Friction Stir Welding (FSW) of two dissimilar alloys (Aluminium alloy) AA2014-T6 and (Magnesium alloy) AZ31B. An investigation has been performed to examine the influence of tool pin profile, rotational speed, and welding speed on the welding characteristics: tensile strength, micro-hardness, and percentage of elongation using the Taguchi method. The Multi-Objective Optimization Method by Ratio Analysis (MOORA) technique has been applied to predict the best values of influencing parameters to obtain the optimum welding characteristics. The maximum tensile strength (386.25 MPa), microhardness (120.9HV), and percentage of elongation (20.79 %) were predicted by the stepped square tool pin profile, 1000 rpm tool rotation, and 60 mm/min welding speed. Energy dispersive spectroscopy (EDS) and Scanning Electron Microscope (SEM) analysis were performed to examine the various metallic elements and microstructures. The best optimal set was used to compare the performance of the proposed process with the conventional process. The tensile strength, percentage of elongation, and microhardness of the proposed method are 18.82 %, 19.89 %, and 42.43 % higher than the conventional method. Graphical Abstract: ga1